PENGARUH POST CURING TREATMENT DAN PERENDAMAN AIR LAUT PADA KOMPOSIT HYBRID KEVLAR/KARBON - Suryono, Ahmad Fauzan; Faizal, Ahmad; Hestiawan, Hendri (UNIB Press, 2020)
In composite engineering, there are also known hybrid composite types which allow the presence of two or more reinforcing particles and are usually arranged by a straight type and a random type. In this research, hybrid composites are made from a combination of kevlar fiber and carbon twill fiber using the vacuum assisted resin infusion (VARI) method. This fiber will be made into a composite consisting of ten layers with a composition of six layers of kevlar fiber and 4 layers of carbon twill fibers. Vinylester resin is used as a matrix on the composite. The hybrid composite material was given post curing treatment and soaked by sea water. From the tensile test results obtained an average ultimate tensile strength (UTS) value of 314.38 MPa at post curing temperature of 100 °C, then the results of compressive test of the kevlar/carbon hybrid composite with ASTM D6641 obtained an average compress strength value of 87.76 MPa at 100 °C postcuring and the results of the kevlar + carbon-vinylester composite shear test with ASTM D5379 obtained an average shear strength value of 20.45 MPa at post curing room temperature.